2021
DOI: 10.1371/journal.pcbi.1008948
|View full text |Cite
|
Sign up to set email alerts
|

Small subpopulations of β-cells do not drive islet oscillatory [Ca2+] dynamics via gap junction communication

Abstract: The islets of Langerhans exist as multicellular networks that regulate blood glucose levels. The majority of cells in the islet are excitable, insulin-producing β-cells that are electrically coupled via gap junction channels. β-cells are known to display heterogeneous functionality. However, due to gap junction coupling, β-cells show coordinated [Ca2+] oscillations when stimulated with glucose, and global quiescence when unstimulated. Small subpopulations of highly functional β-cells have been suggested to con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 72 publications
2
51
0
Order By: Relevance
“…More specifically, different lines of evidence suggest that the functionally most connected cells are metabolically more active (66,67,101,104,144,145). At the same time, our current and previous experimental and model findings that the parameter value distributions and functional behavior of cells are heterogeneous in a rather continuous manner (28-30, 32, 34, 145, 146), with no clear-cut subpopulations, are compatible with the view that only a few cells with extreme parameter values are not necessary for normal b cell activation, coordinated activity, and deactivation (41,122). Again, we would like to underline that the terms "first-responders" and "hubs," as defined in this study, are not the same as "pacemakers."…”
Section: Connecting the Dots: Relations Between Activation Plateau And Deactivationsupporting
confidence: 87%
See 2 more Smart Citations
“…More specifically, different lines of evidence suggest that the functionally most connected cells are metabolically more active (66,67,101,104,144,145). At the same time, our current and previous experimental and model findings that the parameter value distributions and functional behavior of cells are heterogeneous in a rather continuous manner (28-30, 32, 34, 145, 146), with no clear-cut subpopulations, are compatible with the view that only a few cells with extreme parameter values are not necessary for normal b cell activation, coordinated activity, and deactivation (41,122). Again, we would like to underline that the terms "first-responders" and "hubs," as defined in this study, are not the same as "pacemakers."…”
Section: Connecting the Dots: Relations Between Activation Plateau And Deactivationsupporting
confidence: 87%
“…Our data do not imply that the first-responders are in any way necessary for islets to respond to glucose concentrations and that their role is fixed in time. It is reasonable to speculate that the removal or dysfunction of first-responders would make other cells become first-responders (33,41,104,105,122), and recent experimental data corroborated this (54). Even without removal or dysfunction, the metabolic status and physiological features change as b cells mature (123).…”
Section: Activationmentioning
confidence: 90%
See 1 more Smart Citation
“…A scale-free distribution implies that there exists a subset of highly connected nodes, often called "hubs" (4,30). By studying the distribution of the functional network, Johnston et al and others (30)(31)(32) have suggested that 𝛽-cell hub cells have a greater than average influence on the islet and may be preferentially attacked by diabetic conditions, suggesting a possible mechanism behind the loss of pulsatile insulin secretion in diabetes. These 𝛽-cell hubs were also shown to have unique characteristics including high metabolic activity and depolarizing before and repolarizing after the rest of the islet (30,33).…”
Section: Introductionmentioning
confidence: 99%
“…These β -cell hubs were also shown to have unique characteristics including high metabolic activity and depolarizing before and repolarizing after the rest of the islet (30, 33) . However, electrophysiological experiments and computational studies suggest that it is not feasible for one cell or a small population of cells to have disproportionate influence over the Islet (31, 34, 35) . These studies have caused debate over the most accurate topological description of the islet network (36, 37) .…”
Section: Introductionmentioning
confidence: 99%